VD_FINDINFO HC / 2018 / 1155 vom 26. Dezember 2018 - VD Tribunal cantonal (2018)
BAIL À LOYER, LOYER ÉCHELONNÉ, AUGMENTATIONEN GÉNÉRAL, FORMULE OFFICIELLE, ABUS DE DROIT, ADMISSION DE LA DEMANDE, RECOURS JOINT | 2 al. 2 CC, 253 CO, 269c CO, 269d CO, 62 CO